Digital challenges for the welfare state - Werner Eichhorst; Ulf Rinne (Institute of Labor Economics (IZA), 2017)
Digitalization is the buzzword under which profound changes of the labor market can be summarized. Next to automation, i.e., the increasing use of robots, "intelligent" machines and more comprehensive algorithms that is no longer restricted to routine tasks, especially the emerging platform economy may pose significant "digital challenges" for the welfare state. This article sheds light on the potentially eroding foundations of the welfare state, it discusses tools for combating a potential digital divide on the individual level, and it proposes a new institutional perspective on firms, workers, and the welfare state.
Keywords: J08; J24; O33; O38; 330; digitalization; robots; automation; future of work; industry 4.0; technological change; platform economy; welfare state